(untitled) (Medico Legal Update, 2020)
Background: Depression is the most prevalent mental health problem in the world, and it is considered more prevailing in women than in men. It is a recognized mental health problem that adversely impact upon the individual’s ability to function and sufferer’s daily life. Depression is common in people with eating disorders. It has a higher rate in patients with eating disorders than those without eating disorders. Method: This is a descriptive study which included a sample of 50 patients diagnosed with major depressive disorder and having eating disorder behaviors visiting Ali Kamal consultation center for treatment and follow up. A questionnaire developed including Beck Depression Inventory and Garner-Eating Disorder Inventory. Data collected and analyzed using SPSS version 22. Results: The result of this study indicated that there is statistical of interpersonal distrust, interoceptive awareness, and ineffectiveness of Garner-EDI-2 subscales with depression.